Pemberdayaan Masyarakat Desa Jatisari Kabupaten Boyolali Melalui Pengolahan Nata Ubi Jalar Ungu (Ipomoea batatas): Indonesia - Sofyan, Aan; Zulfah, Dewi Nashikhatul; Mandasari, Anita; Zuhri, Thoha Syaifudin (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
Community empowerment can create self-sufficiency in various fields, both in the economic and food fields. The people of Jatisari Village who are members of the PKK have the potential to process various food products including nata made from purple sweet potato extract (Ipomoea batatas). The purpose of this service program is to provide knowledge and skills to the community about the technology for making nata made from purple sweet potato extract with the addition of red beans (Phaseolus vulgaris) as a nitrogen source in the fermentation process. The benefits of this service are that it can provide knowledge and skills in processing and making nata made from purple sweet potato extract. The method of implementing the service program consists of several stages, including the preparation stage, problem identification, pretest, workshop, workshop, posttest, and evaluation. The results of the implementation of the service program show that members of the Jatisari Village PKK have attended training in making nata made from purple sweet potato extract starting from the process of preparing raw materials, concocting various ingredients, to the process of preparing fermentation to produce nata. The evaluation results showed that most of the training participants did not know how to make nata. In addition, the participants also had never practiced making nata, so this dedication program to introduce nata-making technology could add to the knowledge and experience of PKK Jatisari Village members.